2014
DOI: 10.5553/geno/092150772014027001006
|View full text |Cite
|
Sign up to set email alerts
|

Doeloriëntaties en het tijdsperspectief van oudere werknemers: is er een verband met pensioenintenties?

Abstract: Deze studie heeft als doel de relaties te onderzoeken tussen werkgerelateerde temporele focus (d.w.z. gerichtheid Inleiding IntroductieIn Nederland ligt de gemiddelde pensioenleeftijd anno 2011 op 63 jaar (CBS, 2012). Dit betekent dat er nog steeds sprake is van een tendens om met vervroegd pensioen te gaan, dat wil zeggen, reeds voor de pensioengerechtigde leeftijd. In de Nationale Enquête Arbeidsomstandigheden (NEA) wordt sinds 2008 ook gevraagd of werknemers na hun 65ste willen blijven doorwerken. In 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 42 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…Nevertheless, previous research has shown that the psychological and behavioral consequences of individuals' present and future temporal focus differ in fundamental ways when compared to the consequences of individuals' past temporal focus (Shipp & Aeon, 2019;Shipp et al, 2009). For example, individuals with strong preferences for the past tend to favor passive forms of behavior (Peeters et al, 2014;Rabinovich & Morton, 2012), whereas neither individuals' present nor future temporal focus have been empirically linked with these behavioral tendencies. Hence, we submit that a systematic, indepth investigation of supervisor-team (in)congruence in present and/or future temporal focus extends well beyond the scope of this study.…”
Section: The Potential Roles Of Supervisors' and Teams' Present Andmentioning
confidence: 98%
See 1 more Smart Citation
“…Nevertheless, previous research has shown that the psychological and behavioral consequences of individuals' present and future temporal focus differ in fundamental ways when compared to the consequences of individuals' past temporal focus (Shipp & Aeon, 2019;Shipp et al, 2009). For example, individuals with strong preferences for the past tend to favor passive forms of behavior (Peeters et al, 2014;Rabinovich & Morton, 2012), whereas neither individuals' present nor future temporal focus have been empirically linked with these behavioral tendencies. Hence, we submit that a systematic, indepth investigation of supervisor-team (in)congruence in present and/or future temporal focus extends well beyond the scope of this study.…”
Section: The Potential Roles Of Supervisors' and Teams' Present Andmentioning
confidence: 98%
“…These individuals heavily rely on established routines and existing mindsets, and they prefer well-known procedures over new approaches that deviate from the status quo (Karniol & Ross, 1996). Scholars have demonstrated that highly past-focused individuals tend to choose avoidance-oriented goals over approach-oriented ones (Peeters, Schreurs, & Damen, 2014), are less likely to change their behavioral intentions (Rabinovich & Morton, 2012), and report relatively low self-efficacy (Gana, Klein, Saada, & Trouillet, 2013). Accordingly, it is not surprising that highly past-focused individuals are often characterized as indecisive and ineffective (Karniol & Ross, 1996;Shipp & Aeon, 2019).…”
Section: Past Temporal Focus and Its Psychological Consequencesmentioning
confidence: 99%
“…In addition, the results of the study broaden the understanding of the motivation of older employees to keep working [26]. They indirectly indicate that not only the features connected with work itself can affect the willingness to remain in the company, but also the external factors (an ability to act on the market, manage finances), as well as personality traits (for example, the importance of financial status, economic ambitions).…”
Section: Discussionmentioning
confidence: 77%
“…The motivation of older employees to keep working is being studied [16]. Studies show a stronger link between intrinsic motivation (i-e-congruency) and job satisfaction of the older employees [17].…”
Section: Theoretical Frameworkmentioning
confidence: 99%